Free Flaps in Sternal Osteomyelitis After Median Sternotomy: A Center's 12-Year Experience - Georgiou, Iakovos; Ioannou, Christos I.; Schmidt, Jeremias; Eschborn, Johannes; Mostofizadeh-Haghighi, Giw; Infanger, Manfred; Ghods, Mojtaba; Kruppa, Philipp (Journal of Reconstructive Microsurgery, 2023)
Background Adequate treatment of deep sternal wound infections (DSWIs) after open thoracic surgery still presents a major challenge. This study retrospectively analyzes the results of a single center's 12-year experience in treating DSWI, with special emphasis on free flap reconstruction.Methods In this single-center, retrospective study, all patients admitted with the diagnosis of DSWI after open thoracic surgery between 2009 and 2020 were included. A comparative analysis was performed between: (1) pedicled versus free flaps, (2) the center's two workhorse flaps—the pedicled latissimus dorsi (pLD) versus free anterolateral thigh (fALT) flaps, as well as (3) myocutaneous (MC) versus fasciocutaneous (FC) flaps. Primary endpoints were length of hospital stay (LOS) after reconstruction and in-hospital mortality.Results Of a total of 165 patients included, 152 underwent DSWI defect reconstruction with a total of 12 different reconstruction methods. Although the defect size was larger in patients who underwent free flap coverage, and the risk profile in the fALT and FC flap groups was higher, the LOS after reconstruction (in days) did not differ significantly between the groups (pedicled vs. free flaps: 23 vs. 28, p > 0.05; pLD vs. fALT: 24.5 vs. 26, p > 0.05; MC vs. FC flaps: 23 vs. 26, p > 0.05). Also, no significant differences were found in terms of in-hospital mortality when comparing the groups (pedicled vs. free flaps: 11.2 vs. 17.4%, p > 0.05; pLD vs. fALT: 11.5 vs. 12.5%, p > 0.05; MC vs. FC flaps: 12.9 vs. 12.5%, p > 0.05).Conclusion With proper patient selection, free tissue transfer is a valuable alternative in the treatment of sternal dehiscence after a DSWI. Furthermore, our data demonstrate that MC flaps are not necessarily superior to FC flaps in the reconstruction of sternal osteomyelitis defects.
Keywords: deep sternal wound infection; sternal osteomyelitis; sternal dehiscence; free flap reconstruction; chest wall reconstruction; wound infection